A Decade of Digital Economy Research in Education: A Bibliometric and Systematic Review of Trends, Gaps, and Future Directions - Nofriansyah Nofriansyah; Eeng Ahman; Endang Supardi; Neti Budiwati; Nani Sutarni; Dadang Dahlan (AL-ISHLAH: Jurnal Pendidikan, 2025)
The intersection of digital economy and education has gained significant academic attention over the past decade, particularly with the increasing influence of artificial intelligence, big data, and platform-based learning. However, a comprehensive understanding of the field's evolution remains limited. This study conducts a bibliometric and systematic review of 201 peer-reviewed journal articles published between 2014 and December 2024, retrieved from the Scopus database. The PRISMA framework guided the selection process. Bibliometric performance analysis and science mapping were carried out using VOSviewer, RStudio, Excel, and OpenRefine to explore publication trends, key themes, influential authors, and emerging research fronts. Findings reveal three dominant thematic clusters: technological innovation (e.g., economic growth, energy efficiency), advanced technologies (e.g., AI, big data, e-learning), and human-centered education (e.g., equity, curriculum design, sustainability). The number of publications peaked between 2020 and 2022, correlating with global shifts due to COVID-19 and increased digital adoption. Despite strong research output, underexplored areas remain, such as Industry 4.0, ethical AI use, and smart mobility in education. This study identifies critical gaps and suggests future research directions, including the need for inclusive digital infrastructure, ethical governance of educational AI, and sustainable models of digital transformation. A conceptual framework is proposed to guide interdisciplinary inquiry at the intersection of education and the digital economy.